2014
DOI: 10.1371/journal.pone.0111374
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Microbiota is Different in Women with Preterm Birth: Results from Terminal Restriction Fragment Length Polymorphism Analysis

Abstract: Preterm birth is a leading cause of perinatal morbidity and mortality. Studies using a cultivation method or molecular identification have shown that bacterial vaginosis is one of the risk factors for preterm birth. However, an association between preterm birth and intestinal microbiota has not been reported using molecular techniques, although the vaginal microbiota changes during pregnancy. Our aim here was to clarify the difference in intestinal and vaginal microbiota between women with preterm birth and wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
1
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(80 citation statements)
references
References 34 publications
(45 reference statements)
1
72
1
6
Order By: Relevance
“…On the other hand, in animal experiments, the induction of colonic T cells was specific to Clostridium ‐colonized mice and a genus of Clostridium promoted T cell accumulation . In addition, Shiozaki et al reported that lower levels of Clostridium clusters and higher levels of Lactobacillales were observed in the intestinal microbiota in preterm birth patients compared to those in term birth patients and there were no differences in vaginal microbiota between the two groups . Although we did not investigate intestinal microbiota, probiotics formulated with Streptococcus faecalis (10 mg/g), Clostridium butyricum (50 mg/g) and Bacillus mesentericus (50 mg/g) were administered .…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…On the other hand, in animal experiments, the induction of colonic T cells was specific to Clostridium ‐colonized mice and a genus of Clostridium promoted T cell accumulation . In addition, Shiozaki et al reported that lower levels of Clostridium clusters and higher levels of Lactobacillales were observed in the intestinal microbiota in preterm birth patients compared to those in term birth patients and there were no differences in vaginal microbiota between the two groups . Although we did not investigate intestinal microbiota, probiotics formulated with Streptococcus faecalis (10 mg/g), Clostridium butyricum (50 mg/g) and Bacillus mesentericus (50 mg/g) were administered .…”
Section: Discussionmentioning
confidence: 76%
“…Nearly 90% of preterm births resulting from infections are caused by ascending infection via the vagina and abnormal vaginal flora is considered an important factor leading to premature birth. However, current comprehensive bacteriological examination shows no difference in vaginal flora between term and preterm birth . Following these findings, studies in recent years have focused upon the importance of intestinal flora on preterm birth .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…(2014) выявлено относительное сниже-ние количества представителей кластеров Clostridium и Bacteroidetes spp. при увеличении количества представи-телей Lactobacillus в группе преждевременных родов по сравнению с группой срочных родов [13].…”
Section: становление микробиотыunclassified
“…В частности, выявлено относительное снижение количества представителей кластеров Clostridium и Bacteroidetes spp. при увели-чении количества представителей Lactobacillus в груп-пе преждевременных родов по сравнению с группой срочных родов [10]. Возможность поступления бактерий из кишечника матери к плоду подтверждена на животной модели экспериментом с пероральным введением гене-тически меченого штамма Enterococcus faecium бере-менным мышам и последующим обнаружением данного штамма в амниотической жидкости и тканях плода [11].…”
Section: актуальностьunclassified